Toxaris albo O przyjaźni Lukiana z Samosat - ideał czy parodia? - Sowa, Joanna (Vox Patrum, 2019)
LUCIAN’S TOXARIS, OR FRIENDSHIP – IDEAL OR PARODY? SUMMARY The Toxaris of Lucian is a dialogue in form, but its contents are a collection of fabulous and sentimental stories about friendship, related by a Greek Mnesippos and a Scythian Toxaris, to demonstrate the superiority of their respective national groups. Its formal transparency is a problem: it can be interpreted as an entertaining work extolling traditional friendship, or as a typically lucianic parody of the kind of sentimental views of Greek male friendship depicted in romantic novels, as well as popular myth and legend. This paper proposes that in Toxaris Lucian may be using his humour, above all, to challenge common stereotypes about Greeks and “barbarians”, and to show a new form of friendship – that between individuals with similar values, based on their common paideia.